Human capital, knowledge creation, knowledge diffusion, institutions and economic incentives: South Korea versus Africa - Simplice Asongu; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2018)
This article compares African countries to South Korea in terms of knowledge economy (KE). Emphasis is laid on human capital, knowledge creation, knowledge diffusion, institutions and economic incentives. The analytical approach consists of providing knowledge economy catch-up strategies that can be understood within the context of country-specific gaps between the frontier country in KE and laggard African countries. The empirical evidence is based on sigma convergence with data for the period 1996-2010. Overall, a KE diagnosis is provided by assessing KE gaps (between South Korea and specific-African countries) and suggesting compelling catch-up strategies with which to reduce identified gaps. Contemporary and non-contemporary policies from South Korea and more contemporary policies based on challenges of globalisation are discussed. The policy relevance of this inquiry aligns with the scholarly perspective that catch-up between South Korea and more advanced economies was accelerated by the former adapting to and assimilating relatively obsolete technological know-how from more developed nations.
Keywords: O10; O30; O38; O55; O57; 330; Knowledge economy; Benchmarks; Policy syndromes; Catch-up; Africa